2005
DOI: 10.1128/mcb.25.10.4237-4249.2005
|View full text |Cite
|
Sign up to set email alerts
|

The S1P2 Receptor Negatively Regulates Platelet-Derived Growth Factor-Induced Motility and Proliferation

Abstract: Sphingosine-1-phosphate (S1P), a bioactive sphingolipid metabolite, is the ligand for five specific G proteincoupled receptors, named S1P 1 to S1P 5 . In this study, we found that cross-communication between plateletderived growth factor receptor and S1P 2 serves as a negative damper of PDGF functions. Deletion of the S1P 2 receptor dramatically increased migration of mouse embryonic fibroblasts toward S1P, serum, and PDGF but not fibronectin. This enhanced migration was dependent on expression of S1P 1 and sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
105
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(116 citation statements)
references
References 61 publications
8
105
0
3
Order By: Relevance
“…Physiologically, insulin-mediated glycogen synthesis is diminished in response to S1P, suggesting that the sphingolipid mediator may contribute to hepatic insulin resistance keratinocytes via stimulation of the S1P 2 receptor subtype [14]. This is in accordance with a variety of studies indicating that S1P 2 inhibits proliferation in several cells such as mouse embryonic fibroblasts and germinal centre B cells [36,37]. The present study provides evidence that S1P 2 stimulation is able to attenuate insulin-dependent Akt phosphorylation.…”
Section: Discussionsupporting
confidence: 79%
“…Physiologically, insulin-mediated glycogen synthesis is diminished in response to S1P, suggesting that the sphingolipid mediator may contribute to hepatic insulin resistance keratinocytes via stimulation of the S1P 2 receptor subtype [14]. This is in accordance with a variety of studies indicating that S1P 2 inhibits proliferation in several cells such as mouse embryonic fibroblasts and germinal centre B cells [36,37]. The present study provides evidence that S1P 2 stimulation is able to attenuate insulin-dependent Akt phosphorylation.…”
Section: Discussionsupporting
confidence: 79%
“…However, S1PR2 signaling negatively regulates tumor angiogenesis and tumor growth in vivo 43. S1PR2 is also involved in the reduction of platelet‐derived growth factor mediated‐cell motility and proliferation 44. A knockdown in the expression of S1PR2 by shRNA in satellite cells resulted in a twofold increase in cell migration 45.…”
Section: Discussionmentioning
confidence: 99%
“…Increased S1P formation, in turn, activates S1P receptors on the same and͞or neighboring cells in an autocrine or paracrine manner. It has been demonstrated that this type of ''inside-out'' signaling by S1P is critical for migratory responses of fibroblasts and smooth muscle cells toward PDGF (9,12) and human breast cancer cells toward EGF (8). Similarly, S1P secreted by mast cells is important for migration of mast cells toward antigen (Ag) and might be involved in the movement of mast cells to sites of inf lammation (13).…”
mentioning
confidence: 99%